Self-Selection of Interesting Occupation Facilitates Cognitive Response to the Task: An Event-Related Potential Study - Tokuda, Keiichiro; Maruta, Michio; Shimokihara, Suguru; Han, Gwanghee; Tomori, Kounosuke; Tabira, Takayuki (Frontiers in Human Neuroscience, 2020)
Introduction In this study, we examined whether the self-selection of occupations of interest affects reaction times and cognitive processing by using the Aid for Decision-making in Occupation Choice (ADOC) and evented-related potentials (ERP). We also assessed the relationship of these with psychological indicators. Method We extracted 78 occupations from the ADOC in consideration of the subjects’ age, and three conditions were set (1. self-selection of an interesting occupation, 2. self-selection of a disliked occupation, and 3. forced selection).The reaction time task was executed under their conditions during which ERP was measured. We compared P300 component of ERP in these conditions. Moreover, we examined the association of cognitive processing and degree of satisfaction and performance in relation to occupation, with psychological indicators. Results P300 amplitude at Fz significantly increased in the self-selection of an interesting occupation. P300 amplitude at Pz was significantly positively correlated with occupational satisfaction score. Conclusion Self-selection of interesting occupations in the ADOC resulted in increased attentional resource allocation by increasing motivation. Further, there was a positive correlation between satisfaction in relation to the occupation and attentional resource allocation. Therefore, occupational therapists should know which occupations the patients consider interesting and help them to select by themselves, thus enhancing their satisfaction after consultation. These interventions may contribute to promoting motivation and cognitive processing.